اسلامی ریاست میں رائے عامہ کی حیثیت اور حدود : Public Opinion and its Position and Limitation in an Islamic State - Dr Shah Moheen ud Din Hashmi; Hafiz Saeed Ul Rehman (MEI, 2023)
Public opinion has immense importance in the modern era, it even plays important role in the making and unmaking of governments and legislation. Public opinion means the opinion of masses on a particular national or regional issue on which arguments can be made. Public opinion is also important in an Islamic state. The Quran and Hadith contain many instances on this subject, yet there are certain limitations on public opinion in an Islamic State. According to Islamic point of view, there are two kinds of injunctions; one that can be changed as per requirement of time and other that remain constant. The injunctions pertaining to constant or permanent issues do not care about the public opinion, such as worships cannot be changed on the basis of public opinion. The changeable injunctions contain some specific and some public issues. Suggestions and opinions of only experts are welcomed in specific issues, while public opinion is worthwhile in public issues. What is the position of public opinion in changing the government and constitutional changes? What is the importance and limitations of public opinion? This issue must be addressed in the light of paradigm set up by the Islamic State of Madinah. The current paper intends to address these questions